2002
DOI: 10.1046/j.1341-8076.2002.00041.x
|View full text |Cite
|
Sign up to set email alerts
|

The masquerades of female pelvic tuberculosis: Case reports and review of literature on clinical presentations and diagnosis

Abstract: In this review, tuberculosis of the genital tract was diagnosed retrospectively in 11 females over 15 years. The presentations of nine cases are described. Seven of the nine cases presented with ascites, vague abdominal distension, weight loss and were misdiagnosed as ovarian carcinoma. Eight women had no relevant past history. A review on clinical presentations and diagnosis of pelvic tuberculosis is presented. We conclude that although the incidence of tuberculosis is uncommon in developed countries, its pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 16 publications
0
47
0
Order By: Relevance
“…Morgagni first described genital tuberculosis in the mid eighteenth century and the tuberculous bacillus was discovered in 1882 by Koch (1). Tuberculosis is the second most common cause of death worldwide amongst communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Morgagni first described genital tuberculosis in the mid eighteenth century and the tuberculous bacillus was discovered in 1882 by Koch (1). Tuberculosis is the second most common cause of death worldwide amongst communicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although syncytiotrophoblastic giant cells have rarely been described in YST (1), other types of giant cells or granulomatous reaction have not been reported in YST to the best of our knowledge. in the case under study, we found a profound granulomatous reaction in the form of The differential diagnosis of a granulomatous reaction in the ovary includes infections, especially tuberculosis, and non-infective lesions such as sarcoidosis, Crohn's disease, xanthogranulomatous oophritis, foreign body and post-operative granulomas (2)(3)(4)(5)(6)(7)(8). Tuberculosis is an important cause of infertility and tubo-ovarian mass in india.…”
Section: Discussionmentioning
confidence: 80%
“…8,9 The fallopian tubes are affected in almost 100% of the cases followed by the endometrium in 50%, ovaries in 20%, cervix in 5%, and vagina and vulva in <1%. 10,11 Patients with genital tuberculosis are usually young women diagnosed during infertility work up. Genital tuberculosis is rare in postmenopausal women and responsible for only approximately 1% of postmenopausal bleeding, if symptomatic.…”
Section: Discussionmentioning
confidence: 99%